Sureśvara's vārtika on Khila kāṇḍa with half-verse index - Jog, K. P.; Hino, Shoun (Motilal Banarsidass Publishers, 1998)
English translation with index of a supercommentary on Śaṅkarācārya's Bhāṣya on Br̥hadāraṇyakopaniṣad, Hindu philosophical classic.